Live looping in musical performance : lusophone experiences in dialogue - Duarte, Alexsander; Sardo, Susana (Routledge, 2023)
"Live Looping in Musical Performance presents a range of interdisciplinary perspectives on the uses of live looping technology by a range of lusophone performers and composers, considering diverse aspects from the aesthetic component to the instrumentation and even setup. Containing eleven chapters written by musicians and researchers from Portuguese-speaking countries, a range of musical contexts, genres and practices are explored. The novelty of including collaborative texts written alongside non-professional researchers offers the possibility of drawing from real experience to consider how live looping has been changing and "cyborguising" the concept of music, the ritual of the performance, the identity of the musicians and the public's expectations. Live Looping in Musical Performance provides cutting-edge reading for composers and performers, as well as ethnomusicologists, students and researchers working in the areas of music production, technology and performance. This book addresses a broader audience, both academic and non-academic, who are interested in new processes of musical creativity in a post-human world"--